TRADISI BADABUS (RATIB TAJI BESI) PADA MASYARAKAT KELURAHAN TUGUWAJI KECAMATAN TIDORE KOTA TIDORE KEPULAUAN - Ajid Djalal (HOLISTIK, Journal of Social and Culture, 2023)
The richness of cultural diversity will allow the unification of various groups on the basis of equality, both religious and cultural as human rational nature in realizing peace as a form of accommodation between the two naturally and not because it is forced. Thus, religion is a guideline that is used as a framework for interpreting human actions through rituals. The application of culture as an art appreciation can be seen in community traditions both at ritual events and other cultural displays that contain very high artistic value such as the Badabus tradition. Badabus tradition, is a typical art of the community in Tuguwaji Village, Tidore City Islands. This art is often played in funeral homes after funerals for approximately forty-four days and some also carry out thanksgiving celebrations. This tradition is played by two or more people according to the iron prepared, and also the community members who are invited to attend the celebration (invited orally), as well as attend the throne of Debus or the thanksgiving of Badabus. The Badabus tradition is carried out by the people of Tuguwaji Village with great enthusiasm to participate in carrying out attractions, many Tuguwaji people have received tariqa knowledge and learned the values of the Badabus tradition as a way of efforts for the people of Tidore City in general and especially Tuguwaji Village to maintain it. So that this Badabus tradition will not be extinct and always exists to generations of children and grandchildren. Keywords: tradition, badabus, socio-cultural values